Análise da eficácia da fiscalização marítima no combate à pesca ilegal da lagosta no Estado do Ceará - Gomes Filho, Giovanni Pacelli Ferreira (2015)
This study aimed to analyze, using econometric techniques and based in panel data utilization, the efficiency of maritimal fiscalization of illegal lobster fishing activity in Ceara during the period 2012-2013. In conclusion, it was verified that the current fiscalization in the State of Ceara does, is ineffective to prevent predatory lobster fishing in state. And finally, it was suggested that the fiscalization policy needs to be reviewed in order to do the perform the required changes needed for fiscalization improvement.